Uji Kinerja Alat Pemotong Batang Singkong Tipe Double Block Cutter (DBC) pada Tiga Ukuran RPM - Asmara, Sandi; Firmansyah, Aulia Chandra; Kuncoro, Sapto (abe.fp.unila.ac.id, 2023)
This research on the performance test of the cassava stem cutting type Double Block Cutter (DBC) at three RPM sizes aims to determine the working capacity of the cassava stem cutting. The tool used in this study is a stopwatch, tachometer, measuring cup, derrigen, cassava stem seed cutter (Petokong). The materials used in this study were cassava stems and gasoline. This study used a Completely Randomized Facrorial Design (RALF) using two factors, namely the value of the cutting machine rotational speed factor and the factor of the number of inputs of cassava stems, each factor will be tested with three levels (treatment). The value of the rotational speed of the cutting tool was tested with three kinds of rpm, namely rotation speed 1 = 2600 rpm, rotation speed 2 = 3700 rpm, rotation speed 3 = 4800 rpm. The results of this study indicate that an increase in the working capacity of the tool is indicated by the increasing number of cutting seeds during testing with 4 sticks inserted, the effect of engine rpm on the performance test of the Petokong tool has no significant effect on the working capacity of the Petokong tool, the effect of the interaction between rpm and the feeder. cassava stems are only found in fuel consumption, while the working capacity and uniformity of the cut results do not occur interactions. Keywords: Cassava Kasesart, Cassava Seeds, Cassava Stems, Level of Uniformity. Petakong, Rpm.